Pulmonary Vascular Disease and Cardiopulmonary Exercise Testing - Laveneziana, Pierantonio; Weatherald, Jason (Frontiers in Physiology, 2020)
Cardiopulmonary exercise testing (CPET) is useful for clinicians working in the field of Pulmonary Hypertension (PH) in several ways, including: helping with differential diagnosis, evaluating exercise intolerance and its underpinning mechanisms, accurately assessing exertional dyspnea and unmasking its underlying often non straightforward mechanisms, generating prognostic indicators. Pathophysiologic anomalies in PH can range from reduced cardiac output and aerobic capacity, to inefficient ventilation, dyspnea, dynamic hyperinflation and locomotor muscle dysfunction. CPET can magnify the PH-related pathophysiologic anomalies and has a major role in the management of PH patients.